Persistence of Asthmatic Response after Ammonium Persulfate-Induced Occupational Asthma in Mice - Ollé-Monge, Marta; Muñoz, Xavier; Vanoirbeek, Jeroen A. J.; Gómez-Ollés, Susana; Morell, Ferran; Cruz, María-Jesus (PLOS ONE, 2014)
Introduction Since persulfate salts are an important cause of occupational asthma (OA), we aimed to study the persistence of respiratory symptoms after a single exposure to ammonium persulfate (AP) in AP-sensitized mice. Material and Methods BALB/c mice received dermal applications of AP or dimethylsulfoxide (DMSO) on days 1 and 8. On day 15, they received a single nasal instillation of AP or saline. Airway hyperresponsiveness (AHR) was assessed using methacholine provocation, while pulmonary inflammation was evaluated in bronchoalveolar lavage (BAL), and total serum immunoglobulin E (IgE), IgG1 and IgG2a were measured in blood at 1, 4, 8, 24 hours and 4, 8, 15 days after the single exposure to the causal agent. Histological studies of lungs were assessed. Results AP-treated mice showed a sustained increase in AHR, lasting up to 4 days after the challenge. There was a significant increase in the percentage of neutrophils 8 hours after the challenge, which persisted for 24 hours in AP-treated mice. The extent of airway inflammation was also seen in the histological analysis of the lungs from challenged mice. Slight increases in total serum IgE 4 days after the challenge were found, while IgG gradually increased further 4 to 15 days after the AP challenge in AP-sensitized mice. Conclusions In AP-sensitized mice, an Ig-independent response is induced after AP challenge. AHR appears immediately, but airway neutrophil inflammation appears later. This response decreases in time; at early stages only respiratory and inflammatory responses decrease, but later on immunological response decreases as well.